Professional cake decoration / Toba Garrett - Garrett, Toba
The comprehensive guide to amazing cake decoration now fully updated Professional Cake Decorating is a must-have resource for professional and aspiring cake artists, baking and pastry students, and cake decorating hobbyists, drawing on years of experience from master cake designer and IACP Award nominee Toba Garrett.